Alexander McQueen savage beauty - Bolton, Andrew 1966- (Metropolitan Museum of Art Distributed by Yale University Press, 2011)
"The exhibition, organized by The Costume Institute, will celebrate the late Alexander McQueen's extraordinary contributions to fashion. From his postgraduate collection of 1992 to his final runway presentation which took place after his death in February 2010, Mr. McQueen challenged and expanded the understanding of fashion beyond utility to a conceptual expression of culture, politics, and identity. His iconic designs constitute the work of an artist whose medium of expression was fashion. Approximately one hundred examples will be on view, including signature designs such as the bumster trouser, the kimono jacket, and the Origami frock coat, as well as pieces reflecting the exaggerated silhouettes of the 1860s 1880s, 1890s, and 1950s that he crafted into contemporary silhouettes transmitting romantic narratives. Technical ingenuity imbued his designs with an innovative sensibility that kept him at fashion's vanguard." -- MMA website